The Impact of Scarcity on Pro-environmental Behavior in the COVID-19 Pandemic - Sachdeva, Sonya; Wu, James Shyan-Tau; Zhao, Jiaying (Frontiers in Sustainable Cities, 2021)
As the world contends with the far-ranging impacts of the COVID-19 pandemic, ongoing environmental crises have, to some extent, been neglected during the pandemic. One reason behind this shift in priorities is the scarcity mindset triggered by the pandemic. Scarcity is the feeling of having less than what is necessary, and it causes people to prioritize immediate short-term needs over long-term ones. Scarcity experienced in the pandemic can reduce the willingness to engage in pro-environmental behavior, leading to environmental degradation that increases the chance of future pandemics. To protect pro-environmental behavior, we argue that it should not be viewed as value-laden and effortful, but rather reconceptualized as actions that address a multitude of human needs including pragmatic actions that conserve resources especially during scarcity. To bolster environmental protection, systematic changes are needed to make pro-environmental behavior better integrated into people's lives, communities, and cities, such that it is more accessible, less costly, and more resilient to future disturbances.